Medical Treatment for Endometriosis: Tolerability, Quality of Life and Adherence - Barbara, Giussy; Buggio, Laura; Facchin, Federica; Vercellini, Paolo (Frontiers in Global Women's Health, 2021)
Endometriosis is associated with painful symptoms, infertility, sexological difficulties, and psychological suffering. All these symptoms have a negative impact on the overall quality of life of women with the disease, with significant personal, social and economic costs. Several medical options are available to manage symptomatic endometriosis. The pharmacological treatment for endometriosis-related pain may be necessary for decades, or at least until there is a desire for pregnancy or physiologic menopause occurs. In this perspective, clinicians should consider not only the efficacy, but also side effects, tolerability, and costs, along with women's preferences toward different treatments. In this mini-review, we analyzed the pros and cons of the available drugs for the medical therapy of endometriosis, such as estrogen-progestins, progestins, GnRH agonist and GnRH antagonists.